PENGARUH MODEL PEMBELAJARAN GAMIFIKASI BERBASIS POIN TERHADAP MOTIVASI BELAJAR IPAS SISWA KELAS V SD INPRES 12/79 LAKUKANG KECAMATAN MARE KABUPATEN BONE - Sudarto, Sudarto; Abd. Kadir,; Krisnawati, Krisnawati (Jurnal Cakrawala Ilmiah, 2025)
This study is a pre-experiment that aims to determine whether the Point-Based Gamification learning model has an effect or not on increasing the motivation in learn the IPAS of the Fifth Grade students of SD Inpres 12/79 Masukg, Mare District, Bone Regency in science learning. The variables in this study are the Point-Based Gamification learning model and students' IPAS learning motivation. The population in this study were all of the Fifth Grade students of SD Inpres 12/79 Masukg, totaling 20 students. The sampling technique used was saturated sampling. The data from this study were obtained through the provision of questionnaires. The data collection techniques used were observation and questionnaires to determine the students' learning motivation before and after using the Point-Based Gamification learning model. Based on the descriptive statistical analysis, the average pretest and posttest were of 65.95 and 82.25 respectively; based on the inferential statistical analysis, the Sig. value was of 0.00 <0.05, which means that there is a significant difference between the average pretest score and the average posttest. Conclusion: The point-based gamification learning model has a significant effect on increasing the motivation in the learn the IPASof the Fifth Grade students of SD Inpres 12//79 Masukg, Mare District, Bone Regency